Improving English Vocabulary Mastery with the TPR Method Through Realia Media in Elementary School Students - Siregar, Dharma Yunita (Global Education Journal, 2025)
Language is a very important communication tool in human life. Through language, humans can convey their messages, ideas, thoughts, and feelings to others, and with language, we can also channel various information to others. This study aims to improve the mastery of English vocabulary with the TPR method through realia media in grade V students of SD IT Insan Qur'Ani. This research method includes a type of classroom action research with the research subject of 50 students in grade V of SD IT Insan Qur'Ani, totaling 50 students. The design of this study uses the kemmis and taggart models which are carried out in two cycles. The study results show that using the TPR method through realia media can improve students' English vocabulary mastery. The increase in students' English vocabulary mastery can be seen from an increase in the aspect of reciting vocabulary from before the action is carried out to cycle II by 0.48, the increase in the aspect of reading vocabulary from before the action is carried out to the second cycle by 0.48, the increase in the aspect of writing vocabulary from before the action is carried out until the second cycle by 0.48, the increase in the aspect of interpreting vocabulary from before the action is carried out until the second cycle is carried out by 0.16.  The increase in the aspect of using vocabulary in learning from before the action was carried out to the second cycle was 0.48 and the average score obtained before the action was taken was 51.8 with a percentage of completeness of 8%, after the action was carried out in the first cycle the average score of students became 80.4 with a percentage of completeness of 68% during the learning process. After the second cycle of action, the average score of students became 86.4 with a completion percentage of 88% during the learning process.